Ultra-Sensitive Detection of Chloramphenicol by CdS@NiMoS Nanorods-Based Photoelectrochemical Aptasensor - Hebin Sun; Yimeng Sun; Tong Qi; Zhenyu Wang; Jianlong Zhao; Lijuan Liang (Biosensors)
A novel nanomaterial photoelectrochemical aptamer sensor based on CdS@NiMoS heterojunction nanocomposites was constructed for highly sensitive detection of chloramphenicol (CAP) in antibiotic residues. Through optimization of the material synthesis process, the optimal doping ratio of MoS2 to Ni3+ (70% MoS2 and 10% Ni3+) was identified, which significantly enhanced the photogenerated carrier separation efficiency. In thin-film preparation, comparative analysis of four film-forming methods led to the determination of an optimal process with stability. To achieve highly specific CAP detection, the nanocomposite chip was integrated with nucleic acid aptamer biorecognition elements within a standard three-electrode detection system. Experimental results demonstrated a linear response (R2 = 0.998) in the 0.1–2 μM concentration range, with a detection limit of 3.69 nM (3σ/S).